Prevalence of Adverse Birth Outcomes and their Association with Maternal Characteristics - Patience Ndidi Amadi; Folorunso Dipo Omisakin; Tamunotonye W. Jacks; Helen Wama; Mercy Mgbere (International Journal of Global Health and Epidemiology, 2026)
Background: Adverse birth outcomes remain important contributors to maternal and neonatal morbidity and mortality, particularly in low- and middle-income countries. Maternal characteristics, pregnancy complications, lifestyle practices, and socioeconomic conditions may influence pregnancy outcomes. This study assessed the prevalence of adverse birth outcomes and examined their association with selected maternal characteristics among women attending postnatal clinics in primary healthcare facilities in Rivers State, Nigeria. Methods: A cross-sectional descriptive study was conducted among 454 women aged 15–49 years who had delivered within the preceding 12 months and attended selected primary healthcare facilities across the three senatorial districts of Rivers State. Participants were recruited using a multistage sampling technique. Data were collected using a structured interviewer-administered questionnaire and analysed using SPSS version 27.0. Frequencies and percentages were used to describe adverse birth outcomes, while Pearson's Chi-square test examined associations between maternal characteristics and outcomes. Statistical significance was set at p < 0.05. Results: Preterm birth was the most prevalent adverse birth outcome (31.1%), followed by macrosomia (25.6%) and neonatal death (24.7%). Miscarriage occurred in 19.8% of respondents, while low birth weight, stillbirth, and child abnormalities were reported in 16.5%, 14.5%, and 11.5%, respectively. Vaginal bleeding was significantly associated with preterm birth (50.4%), stillbirth (26.4%), miscarriage (33.1%), macrosomia (41.3%), and child abnormalities (16.5%). PROM was significantly associated with preterm birth (50.0%), stillbirth (20.0%), miscarriage (27.5%), and macrosomia (42.5%). Alcohol consumption and herbal medicine use were significantly associated with most adverse outcomes. Diabetes, hypertension, and maternal age were also significantly associated with selected outcomes. Conclusion: Adverse birth outcomes were common among the study participants and were associated with several maternal and pregnancy-related characteristics. Strengthening antenatal screening, early identification and management of pregnancy complications, maternal health education, and timely referral at primary healthcare facilities may help reduce adverse birth outcomes in Rivers State